Pelatihan Manajemen Stres Berbasis Mindfulness: Efektivitas Pendekatan MBSA CR8+ terhadap Peningkatan Strategi Koping Positif Tenaga Kerja Indonesia di Hong Kong - Mochamad Nursalim; Wulan Patria Saroinsong; Sherrin Nurlita Widya; Ricky Setiawan; Ni Made Marlin Minarsih; Nanda Audia Vrisaba; Hitta Alfi Muhimmah; Shelly Andari; Dhian Gowinda Luh Safitri; Vania Ardelia; Ima Widiyanah (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2026)
Indonesian migrant workers (TKI) in Hong Kong face significant psychological stress due to heavy workloads, social isolation, and cultural adaptation pressures. Limited access to mental health services exacerbates this condition. This community service program aims to improve the stress management skills of Indonesian migrant workers through the Mindfulness-Based Stress Approach (MBSA) CR8+. The program was implemented comprehensively with a training design using a participatory and educational approach that was oriented towards increasing individual capacity in managing stress through mindfulness techniques. This training was attended by 200 participants.. The intervention included online training (Zoom and Google Classroom) and offline training in Hong Kong, with the MBSA CR8+ module covering mindfulness techniques, progressive relaxation, emotion regulation, and guided breathing. Pre-test results showed that 45% of participants experienced high stress and 40% experienced moderate stress, with the dominant complaints being heavy workloads (55%) and limited rest time (48%). Post-test results showed a decrease in physical symptoms (40% to 35%) and negative emotions (30% to 25%), as well as a significant increase in positive coping strategies from 10% to 20%. The MBSA CR8+ approach has been proven effective in increasing self-awareness and stress regulation in Indonesian migrant workers. This model has potential for replication in migrant worker communities in other countries. This program produces a mindfulness-based training module that can be sustainably adopted by community partners.